Integrated TPACK–CRT learning design for elementary schools: Empirical study and conceptual framework development - Kufita Rachman; Haryadi Haryadi; Bernadus Wahyudi Joko Santoso (Indonesian Journal of Curriculum and Educational Technology Studies, 2025)
21st-century learning demands integration between technology, pedagogy, content, and cultural context to make the learning process more meaningful, reflective, and inclusive. This research aims to analyze the needs of elementary school students and the readiness of teachers in implementing TPACK-CRT-based learning and to develop a conceptual design for TPACK-CRT learning as an integrative framework. The research employs a mixed-methods approach, combining quantitative and qualitative elements, involving 40 elementary school students and 3 teachers. Data was collected through questionnaires and the synthesis of TPACK and CRT theories, which were then analyzed using descriptive analysis and conceptual framework building. The results indicate that both student needs and teacher readiness fall into the high category; however, there are differences in orientation: students demand more contextual use of technology, while teachers demonstrate higher readiness in pedagogical and affective aspects. Based on the synthesis results, a conceptual design for TPACK-CRT learning was developed, comprising four main phases: contextual orientation, meaningful technology integration, cultural interaction and collaboration, and humanistic reflection and relevance. This research contributes to strengthening the theoretical framework of TPACK-CRT integration and provides practical guidance.